'Food allergy? Ask before you eat': Current food allergy training and future training needs in food services. (June 2020) - Soon, J.M.
Abstract: The incidence of allergic reactions to food occurring in eating out situations is becoming increasingly prevalent amongst susceptible consumers. Previous studies repeatedly identified food allergy knowledge gaps among foodservice staff. This highlights the importance of food safety and food allergy training in foodservices to minimise risk of food allergic reactions. This study aims to determine the current food allergy training practices, challenges and future food allergy training needs of foodservices in England. A postal survey was conducted among 500 foodservice operators in North West England. The questionnaire is divided into 5 sections: (i) demographics; (ii) current food allergy training practices; (iii) importance of food allergy training topics; (iv) challenges faced by restaurants when training foodservice staff; and (v) future food allergy training. Out of the 30 restaurants, only one restaurant did not carry out food allergy training. More than 70% of the restaurants frequently trained newly hired staff and whenever changes or updates occurred in the food hygiene regulations (60%). Most of the training were on-the-job training and took between 1 and 2 h to complete. Identification of food allergens in menu, prevention of cross contact and communication were identified as the most important topics in food allergy training. High staff turnover and lack of time contributed to the difficulty in training foodservice staff. There was considerable interest in the types of future food allergy training and most preferred on-site training by authorised staff or training at local councils. Further work is needed in the evaluation of future food allergy training needs to develop effective training materials and delivery methods to ensure the safety of food allergic individuals. Highlights: Most food allergy training was conducted using a one-to-one, on-the-job training approach. High staff turnover and lack of time contributed to the difficulty in training foodservice staff. Communication, prevention of cross contact and identifying food allergens were key topics. Restaurants felt that the responsibility for food allergy training lay with the local council. Face-to-face or on-site training was preferred to online learning.